TEORI FRAUD PENTAGON dan DETEKSI KECURANGAN PELAPORAN KEUANGAN - Nova Novita (Jurnal Akuntansi Kontemporer, 2019)
The purpose of this research is to investigate whether the fraud pentagon theory predictors, namely: Pressure, Opportunity, Rationalization, Capability and Arrogance able to explain the probability of financial statement of fraud occurrence in Indonesia. The results show that: only Pressure and Rationalization elements can define the likelihood of financial statement fraud. The Capability and Arrogance proxies proposed in this research are not proven to explain the opportunities for financial statement fraud. This research finding shows that the fraud pentagon theory still needs testing in different contexts.